Histories of Tax Evasion, Avoidance and Resistance - Schönhärl, Korinna; HÜRLIMANN, Gisela; Rohde, Dorothea (Financial History, 2023)
Tax evasion, tax avoidance and tax resistance are widespread phenomena in political, economic, social and fiscal history from antiquity through medieval, early modern and modern times. Histories of Tax Evasion, Avoidance and Resistance shows how different groups and individuals around the globe have succeeded or failed in not paying their due taxes, whether in kind or in cash, on their properties or on their crops. It analyses how, throughout history, wealthy and poor taxpayers have tried to avoid or reduce their tax burden by negotiating with tax authorities, through practices of legal or illegal tax evasion, by filing lawsuits, seeking armed resistance or by migration, and how state authorities have dealt with such acts of claim making, defiance, open resistance or elusion. It fills an important research gap in tax history, addressing questions of tax morale and fairness, and how social and political inequality was negotiated through taxation. It gives rich insights into the development of citizen-state relationships throughout the course of history. The book comprises case studies from Ancient Athens, Roman Egypt, Medieval Europe, Early Modern Mexico, the Ottoman Empire, Nigeria under British colonial rule, the United Kingdom of the early 20th century, Greece during the Second World War, as well as West Germany, Switzerland, Sweden and the United States in the 20th century, including transnational entanglements in the world of late-modern offshore finance and taxation. The authors are experts in fiscal, economic, financial, legal, social and/or cultural history. The book is intended for students, researchers and scholars of economic and financial history, social and world history and political economy. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Share Alike 4.0 license.